THIRD WORLD WOMEN AND THE INTERAMERICAN SYSTEM OF HUMAN RIGHTS - Frisso, Giovanna Maria (Unoesc International Legal Seminar, 2017)
The article investigates to what extent the rules of the inter-American human rights system, as well as the interpretation of these standards reflects the struggle of women in the Third World. In this sense, the article discusses initially the particular category of Third World Women and subsequently focuses on the way in which violence as women have been treated in the inter-American human rights system.